Penggunaan Pemetaan Konsep Materi Pelajaran Oleh Guru Untuk Meningkatkan Pemahaman Belajar Seni Musik Secara Daring Di Kelas X-2 SMA Negeri 1 Sitiung - Syarif Hidayatullah; Yos Sudarman (FBS Universitas Negeri Padang, 2021)
This study aims to describe the use of material concept mapping by teachers to help students understand theoretically music subject. The literature review used in this research is related to the notion of school instruction; learning during a pandemic; Learning of cultures and Arts (music) according to K13; and conceptual mapping of subject matter. This research belongs to a quantitative research using a descriptive analysis approach. Based on the research results during three online learning meetings in class X-2, it can be explained that the use of concept mapping of music art subject matter by the teachers based on the concept map made on the blackboard and PowerPoint slides has encouraged an increase in student understanding especially in terms of mastering the materials. The concept mapping made by teachers and assigned to students helps students better understand the subject matter of music in a more structured and organized way. Thus, it is in accordance with the theoretical ideas of the subject matter studied.